2018
DOI: 10.1002/jhet.3131
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of New Benzofuran‐based Thiazoles and Investigation of their Cytotoxic Activity Against Human Breast Carcinoma Cell Lines

Abstract: A new series of 1,3-thiazole-benzofuran derivatives was synthesized via heterocyclization of 2-(1-(6-alkoxy-4,7-dimethoxybenzofuran-5-yl)ethylidene)-2-methyl-2l4-diazane-1-carbothioamides with hydrazonoyl halides. Also, 1-(4,7-dimethoxybenzofuran-5-yl)-3-phenylprop-2-en-1-one derivatives were used for synthesis of another series of 1,3-thiazole-pyrazole-benzofuran. The structure of the newly synthesized products was elucidated via elemental analysis, spectral data, and alternative routes whenever possible. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The last years of the research have confirmed that thiazole scaffold has diverse biological properties that can be used to treat many diseases, such as microbial infections (Bikobo et al 2017;Secci et al 2012;Łączkowski et al 2018a, 2018bZaki et al 2018;Ansari et al 2018), Parkinson's disease (Carradori et al 2018), cancer (de Santana et al 2018;Łączkowski et al 2014, 2016a, 2016bPiechowska et al 2019;Gomha et al 2018), epilepsy (Siddiqui and Ahsan 2010;Ahangar et al 2011;Łączkowski et al 2016a, 2016b, toxoplasmosis (Schultz et al 2014;Łączkowski et al 2018a, 2018b, and antioxidants (Geronikaki et al 2013;Djukic et al 2018). Considering the above-mentioned findings, we decided to design and synthesize the structure of hybrids incorporating both the thiazole ring and the cyclohexenyl moiety.…”
Section: Introductionmentioning
confidence: 98%
“…The last years of the research have confirmed that thiazole scaffold has diverse biological properties that can be used to treat many diseases, such as microbial infections (Bikobo et al 2017;Secci et al 2012;Łączkowski et al 2018a, 2018bZaki et al 2018;Ansari et al 2018), Parkinson's disease (Carradori et al 2018), cancer (de Santana et al 2018;Łączkowski et al 2014, 2016a, 2016bPiechowska et al 2019;Gomha et al 2018), epilepsy (Siddiqui and Ahsan 2010;Ahangar et al 2011;Łączkowski et al 2016a, 2016b, toxoplasmosis (Schultz et al 2014;Łączkowski et al 2018a, 2018b, and antioxidants (Geronikaki et al 2013;Djukic et al 2018). Considering the above-mentioned findings, we decided to design and synthesize the structure of hybrids incorporating both the thiazole ring and the cyclohexenyl moiety.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have examined the antimicrobial activity of quinoline ring‐bearing compounds against existing bacteria and have reported that certain derivatives are more effective than standard drugs (Collin et al, 2011). Previously, the hydrazone moiety has been reported as a well‐known pharmacophoric group for antitubercular and antibacterial (Abdelrahman et al, 2017; Kassab et al, 2021; Sharma et al, 2020), antifungal (Ouf et al, 2018), anticancer (Gomha, 2018; Gomha et al, 2020; Sayed et al, 2021), antiviral (Abu‐Melha et al, 2020; Tian et al, 2022) activities, and carbonic anhydrase inhibitors (Wassel, Ammar et al, 2021). It has been reported that compounds containing arylidene hydrazide structure may exist as E/Z geometrical isomers about C=N double bond and cis/trans amide conformers around amide function (‐CONH‐).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the radicals present on the heterocycle, the organic compounds that contain in their molecule 1,3,4-thiadiazole and 1,2,4-triazole heterocycles have gained a remarkable interest due to their different biological properties, such as: antibacterial [ 3 , 4 , 5 ], antifungal [ 6 , 7 , 8 , 9 ], tuberculostatic [ 10 , 11 ], analgesic [ 12 , 13 ], anti-inflammatory [ 14 , 15 ], hypnotic and sedative [ 16 ], cardioprotective [ 17 ], anticancer [ 18 , 19 , 20 , 21 , 22 ], anti-ulcerative [ 23 ], anticonvulsant [ 24 ], antidiabetic agents [ 25 ], allosteric modulators [ 26 ], and cathepsin B and tubulin inhibitors [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%